Evaluasi Perhitungan Harga Pokok Produksi Menggunakan Metode Full Costing Sebagai Dasar Penetapan Harga Jual (Studi Kasus Pada UKM A.Zaki Bakery) - Sri Mulyani; Kamilah Kamilah (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2023)
Every company definitely wants the expected profit to be achieved from sales activities. Therefore the company is required to be able to set a competitive selling price amidst the many competitors. In setting an accurate selling price, it is necessary to calculate the exact and comprehensive cost of goods, namely by using the full costing method. The full costing method is long term to maintain the stability of the company. The purpose of this study is to find out how the method of calculating the cost of production and selling prices is set by UKM A.Zaki Bakery. And to find out how the selling price is obtained from the calculation of the cost of production using the cost plus pricing method with a full costing approach. The data analysis technique used is a qualitative descriptive analysis technique. This research was conducted at UKM A.Zaki Bakery Medan with the types of data used, namely primary and secondary data. The results of this study indicate that the cost of production uses the company's method, which is Rp669 per piece of bread and the price is set at Rp750 per piece. While the calculation of the cost of production uses the full costing method of Rp678 per pcs and the selling price is determined using the cost plus pricing method with a full costing approach of Rp660. The difference between the selling price set by the company and the selling price determined through the cost plus pricing method is Rp10.